2022
DOI: 10.3389/fbioe.2022.1018653
|View full text |Cite
|
Sign up to set email alerts
|

Effect of myopia and astigmatism deepening on the corneal biomechanical parameter stress-strain index in individuals of Chinese ethnicity

Abstract: Purpose: To investigate the differences in corneal biomechanical parameter stress–strain index (SSI) among different degrees of myopic eyes in Chinese individuals and to analyze the relevant factors of the SSI.Methods: This study analyzed the right eyes of 240 participants (240 eyes) aged 18–34 years. The participants were divided into low-, moderate-, high-, and ultra-high myopia groups according to their spherical equivalent (SE), with 60 eyes included in each group. Spherical, cylinder, and SE were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
3
7
0
Order By: Relevance
“…An interesting finding was that our model's intermediate quantity AL emmetropia , which represented the axial extension of the "non-myopic component" in the model, was positively correlated with SSI. As per the mathematical estimation model, ΔAL is responsible for the larger weight factor of the negative correlation between AL and SSI, which clarifies why the correlation between SSI and AL is not significant as compared to SER, especially as AL is extended (Liu et al, 2022) (Chu et al, 2022) (Liu et al, 2021). However, according to the AL emmetropia formula, SSI is correlated with AL emmetropia , which indicates that SSI is correlated with the corneal curvature of the front surface, and rationally, as a material index, SSI should be independent of corneal geometry to estimate the material stiffness as per the original publication (of SSI) (Eliasy et al, 2019).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…An interesting finding was that our model's intermediate quantity AL emmetropia , which represented the axial extension of the "non-myopic component" in the model, was positively correlated with SSI. As per the mathematical estimation model, ΔAL is responsible for the larger weight factor of the negative correlation between AL and SSI, which clarifies why the correlation between SSI and AL is not significant as compared to SER, especially as AL is extended (Liu et al, 2022) (Chu et al, 2022) (Liu et al, 2021). However, according to the AL emmetropia formula, SSI is correlated with AL emmetropia , which indicates that SSI is correlated with the corneal curvature of the front surface, and rationally, as a material index, SSI should be independent of corneal geometry to estimate the material stiffness as per the original publication (of SSI) (Eliasy et al, 2019).…”
Section: Discussionmentioning
confidence: 82%
“…The stress-strain index (SSI) is a corneal biomechanical parameter provided by Corvis ST Tonometry to evaluate the stiffness of corneal materials, which can intuitively and quantitatively reflect the stressstrain relationship in corneal materials (Eliasy et al, 2019). Previous research has confirmed that a decreased SSI is associated with high myopia based on SER (Liu et al, 2022). As a morphological variable related to axial myopia, theoretically, AL should correlate more with SSI than SER because AL elongation may be caused by a decrease in scleral stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we found that SE was independently correlated with SSI, and we found a statistically significant difference in SSI between the mild, moderate myopia, and extreme myopia groups, consistent with the findings of Han et al, 18 who found that SSI values were lower in patients with higher grades of myopia; however, in their study, they included only two groups: the low myopia group with SE ≥ 3.00D and the high myopia group with SE > −6.00D, which is also consistent with other studies that involved extreme myopia patients among the Chinese population. 23 , 27 ,…”
Section: Discussionmentioning
confidence: 99%
“…12 A better understanding of corneal biomechanical characteristics in different grades of myopia might help improve the selection of suitable candidates for refractive procedures and guide the understanding of the management of biomechanic-modulating treatments. 13,14 Many studies 15,[16][17][18][19][20][21][22][23][24][25][26][27] have been conducted to detect the associations between corneal biomechanics measurements using Corvis ST in China, India, and Iran with few studies incorporating extreme myopia cases and few have addressed the value of SSI. The current study is the first to describe corneal biomechanical properties in different grades of myopia in our country and found that SSI and Peak distance were independently correlated with refractive error spherical equivalent, and SP-A was independently correlated with the grade of myopia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent cross-sectional studies found that eyes with higher myopia have lower corneal stiffness [ 9 , 10 ] and may be less stable and more susceptible to stress [ 11 13 ]. Similarly, in a cross-sectional study conducted by Liu et al, it was observed that the SSI value exhibited a sequential decrease when categorized according to the degree of myopia, namely, low, moderate, high, and ultra-high [ 14 ]. The difference in the rate of change of spherical equivalent (SE) refractive error may be related to the change in corneal stiffness and needs to be investigated in a longitudinal study.…”
Section: Introductionmentioning
confidence: 99%